PEMIKIRAN HADITS KAMARUDIN AMIN - Maliki Maliki; Husnul Hidayati (UIN Mataram, 2019)
This paper discusses the thoughts of Hadist Kamarudin Amin by using the method of analyzing Isnad Cum Matan, various Isnad and different texts that have proven to be effective research tools for reconstructing history to distinguish between authentic and false history. In other words, in examining the transmission of science in the early days of Islam, matan's analysis, which compares the variants of the text, seems to be as important as isnad analysis. Departing from the phenomenon that was born from the Historitas sanad hadith study, it was found a number of sanad who appeared to have many rowis, but apparently the rowi-rowi narrated and the path met a rowi, therefore Kamarudin Amin saw hadiths from the other side to dig up the meaning of hadith from sanad and matan to reconstruct from the history of matan and sanad to the rasullallah Saw.